2013
DOI: 10.1002/micr.22208
|View full text |Cite
|
Sign up to set email alerts
|

Continuous high‐dose vasopressors in free anterolateral thigh flap transfer for pharyngeal reconstruction: A report of two cases

Abstract: Use of vasopressors is controversial in patients undergoing free flap reconstruction. Recent literature has suggested that it is safe to administer vasopressors intraoperatively during these procedures. However studies have not addressed whether this safety extends to continuous high dose use. We present two cases of patients who underwent surgery for squamous cell carcinoma of the pharyngeal region, requiring laryngopharyngectomy. Both had pharyngeal reconstruction with a free anterolateral thigh (ALT) flap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The variability of the types of free flaps utilized in this study enhances its generalizability to the field of head and neck free flap reconstruction as a whole. Overall these results are consistent with multiple other clinical studies examining pressors in head and neck reconstruction (Chao, Taylor, Rahmati, & Rohde, 2014; Harris et al, 2012; Kelly et al, 2014; Monroe et al, 2010; Monroe et al, 2011), as well as larger studies evaluating the effect of vasopressors in free flap reconstruction of the breast, head and neck, extremities, and trunk (Table 4; Chan, Chow, & Liu, 2013; Chen et al, 2010; Fang et al, 2018; Knackstedt, Gatherwright, & Gurunluoglu, 2019; Nelson et al, 2017). The study by Nelson et al (2017) observed retrospectively that within 682 patients undergoing 1,039 flaps for breast reconstruction there was no increase in intraoperative thrombotic events (arterial or venous) or flap loss associated with vasopressor administration, but they did have a higher rate of minor complications (wound healing issues, seroma, infection, partial flap loss, and fat necrosis): 53% in the vasopressor group and 43% in those who did not receive vasopressors.…”
Section: Discussionsupporting
confidence: 91%
“…The variability of the types of free flaps utilized in this study enhances its generalizability to the field of head and neck free flap reconstruction as a whole. Overall these results are consistent with multiple other clinical studies examining pressors in head and neck reconstruction (Chao, Taylor, Rahmati, & Rohde, 2014; Harris et al, 2012; Kelly et al, 2014; Monroe et al, 2010; Monroe et al, 2011), as well as larger studies evaluating the effect of vasopressors in free flap reconstruction of the breast, head and neck, extremities, and trunk (Table 4; Chan, Chow, & Liu, 2013; Chen et al, 2010; Fang et al, 2018; Knackstedt, Gatherwright, & Gurunluoglu, 2019; Nelson et al, 2017). The study by Nelson et al (2017) observed retrospectively that within 682 patients undergoing 1,039 flaps for breast reconstruction there was no increase in intraoperative thrombotic events (arterial or venous) or flap loss associated with vasopressor administration, but they did have a higher rate of minor complications (wound healing issues, seroma, infection, partial flap loss, and fat necrosis): 53% in the vasopressor group and 43% in those who did not receive vasopressors.…”
Section: Discussionsupporting
confidence: 91%
“…5 Case reports have documented survival of head and neck free flaps even in the setting of continuous highdose vasopressors. 56,57 Some agents, namely dobutamine 48,50,51 and norepinephrine, 48,49 appear to be have beneficial effects on flap blood flow; hence, their indications and safe dosing limits need to be further clarified. In contrast, epinephrine can decrease flap flow and should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…28 In contrast to the above studies looking at intraoperative vasopressor use, Chao et al reported two cases demonstrating safe use in pharyngeal anterolateral thigh flap reconstruction with continuous high doses extending late into the postoperative setting. 29 Our group has previously demonstrated that vasopressors can be a useful tool to initiate blood flow in recipient vessels if the patient experiences relative intraoperative hypotension. 31 With evidence that vasopressors are safe to administer in head and neck free tissue transfer, identifying the optimal medication to use is important.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these pervasive attitudes concerning vasopressors in free tissue transfer, multiple experimental and clinical studies have demonstrated increased flap blood flow with the use of various vasoactive medications [18][19][20][21][22] and no overall effect on flap outcomes. [22][23][24][25][26][27][28][29][30][31] The purpose this study is to address the following question: among patients undergoing head and neck free flap reconstruction, does the use of vasoactive medication intraoperatively, as compared with no use, increase the rates of free flap failure and complications? We hypothesize that the rates of free flap failure and complications in subjects receiving vasopressors intraoperatively during head and neck microsurgical reconstruction are equivalent to those not receiving vasopressors.…”
mentioning
confidence: 99%